Daily growth and length-weight relationship ofLates calcarifer (Bloch) larvae during hatcheryrearing - Kailasam, M; Thirunavukkarasu, A R; Sundaray, J K; Abraham, Mathew; Sarada, C; Subburaj, R; Thiagarajan, G; Karaiyan, K (Indian Journal of Fisheries, 2011)
Daily growth and length-weight relationship of Asian seabass Lates calcariferwas studied in the hatchery reared larvae. Larvae attained mean total length,standard length and total wet weight of 10.96±0.49mm, 8.97±0.47mm and31.93±3.63mg respectively at the age of 21 days of post hatching. Growth ratewas higher when the feed was changed from rotifer (Brachionus plicatilis) toArtemia nauplii and Artemia biomass with increased size variation among thelarvae. The correlation coefficient of total length with total weight and standardlength with total weight were highly significant. Log transformed regressionwere used to study the length-weight relationship. Total length- weight andstandard-length weight relationship indicated the allometric growth in seabasslarvae during hatchery rearing phase.